2015
DOI: 10.1016/j.cmpb.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Polyp-Alert: Near real-time feedback during colonoscopy

Abstract: We present a software system called "Polyp-Alert" to assist the endoscopist find polyps by providing visual feedback during colonoscopy. Polyp-Alert employs our previous edge-cross-section visual features and a rule-based classifier to detect a polyp edge-an edge along the contour of a polyp. The technique employs tracking of detected polyp edge(s) to group a sequence of images covering the same polyp(s) as one polyp shot. In our experiments, the software correctly detected 97.7% (42 of 43) of polyp shots on 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…Endoscopy is the most common method for identifying colon polyps and several studies have shown that automatic detection of image regions which may contain polyps within the colon can be used to assist specialists in order to decrease the polyp miss rate [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
“…Endoscopy is the most common method for identifying colon polyps and several studies have shown that automatic detection of image regions which may contain polyps within the colon can be used to assist specialists in order to decrease the polyp miss rate [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
“…This system, called Polyp-Alert [52], is able to give near real-time feedback during colonoscopies. It uses an advanced edge-finding procedure to locate visual features and a rule-based classifier to detect an edge along the contour of a polyp.…”
Section: Related Workmentioning
confidence: 99%
“…The approach from Wang et al [52] is the most recent and probably best-working system in the field of polyp detection. This system, called Polyp-Alert [52], is able to give near real-time feedback during colonoscopies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Such decision support systems are often called CAD (Computer Aided Diagnosis) systems and are already used to some extent in clinical practice. In general, CAD systems strive to be real-time capable to provide immediate feedback during the examination, e.g., [261]. If the physician misses a suspicious structure, the system can highlight the corresponding region to indicate that it should be investigated in detail and maybe a biopsy should be taken.…”
Section: Diagnostic Decision Supportmentioning
confidence: 99%